Car-to-car communication interworking between 5G cellular and DSRC technologies - Ong, Wei Hong (Nanyang Technological University, 2022)
In recent decades, the advancement of wireless communications has brought forth a host of innovative applications, with Intelligent Transportation Systems (ITS) emerging as an important technology that has the potential to prevent up to 82% of traffic accidents. Through Vehicle-to-Everything Technology (V2X), vehicles equipped with On-Board-Units (OBU) transmit safety information such as speed and heading to other vehicles and other nodes in the transportation network such as traffic lights, exchanging vital information and warning drivers of potential hazards on the road. Two technologies have emerged for ITS, namely Dedicated Short Range Communication (DSRC) and Cellular-Vehicle to Everything (CV2X). However, both technologies operate on the 5.9 GHz band, resulting in significant adjacent channel interference with simultaneous usage. This paper aims to investigate CV2X Adjacent Channel Interference on DSRC transmission quality, through measurements done in various scenarios such as indoor versus outdoor, Line-of-Sight (LOS) and Non-Line-of-Sight (NLOS), and the variance of CV2X Interferers. Performance indicators such as Signal-to-Interference-Noise Ratio (SINR) and Packet Delivery Rate (PDR) were measured and computed. Based on our investigations, it was found that the PDR-SINR relationship remains relatively constant for a certain Channel Busy Percentage (CBP) range and is independent of the LOS or NLOS case. For a DSRC-CV2X Hybrid solution to be realised, SINR compliance will need to be implemented in urban areas where high traffic is expected, to ensure PDR falls within an acceptable range.